LEGO® Mindstorms® NXT: The Mayan Adventure - Kelly, James Floyd (Apress, 2012)
This book is fairly unique, and I’ll tell you why. For the earlier version of Mindstorms (called Mindstorms Robotics Invention System, or RIS for short), numerous books were written, most of which focus on building rather extravagant robots, hacking the Mindstorms processor (called the Brick), and doing other wild things with the product. And the books are great! Many of them show you, step by step, how to build and program very unique creations. But after reading them, I felt that a few things were missing. The first thing I noticed was a minimal amount of “where to start” type information. The first time you open up a Mindstorms robotics kit, you might feel a little overwhelmed at the sheer number of pieces (almost all of them small) in the box. You get an instruction manual and some sample robots to build, but there is very little information for those new designers who are asking “How do I start designing a robot?” The second item I found lacking was incentive. There are lots of robots that can be built, but many Mindstorms owners get stuck trying to come up with a problem to solve. “What should I build?” is a frequently asked question. There are robotics competitions, with fixed tasks to complete and well-defined conditions for winning, but what if you’re not into competitions or lack access to them? Where can a person find challenges to take on and accomplish? The last gap involves training. Many of the books on the market for the RIS are great at telling you how to build and program your robots, but many times the explanations aren’t really explanations—they’re instructions: “Put this piece here” and “Drop that there.” What is missing are the reasons for doing something (or, at least, the authors’ reasons).;